Tio2 powder photocatalyst from sol-gel route and its immobilisation with cement for photocatalytic phenol removal - Ahmad Tarmizi, Nor Hafizah; Jamal, Parveen; Mohamed Ismail, Abdul Karim; Sopyan, Iis (The Instituition of Engineers Malaysia, 2009)
Two types of TiO2 powders of water-to-TPT ratios (Powder 1: water/TPT = 1 and Powder 2: water/TPT= 2) were synthesized via sol-gel method. The effect of hydrolysis degree on the formation of TiO2 powder particles was investigated using various physical-chemical characterization methods. The synthesized powders were then immobilised by mixing them with cement to be cement-bonded TiO2 photocatalyst. For photocatalytic measurement, phenol solution was selected as a model of pollutant to be degraded by both cement-bonded TiO2 photocatalysts to analyse their photocatalytic efficiency. The photodegradation of phenol test revealed cement-bonded TiO2 Powder 2 was more efficient than Powder 1 due to its high crystallinity which can lead to faster charge separation and the increased number of phenol molecules adsorbed.